A systematic review of the pathophysiology of 5-fluorouracil-induced cardiotoxicity - Polk, Anne (BioMed Central, 2014)
BACKGROUND: Cardiotoxicity is a serious side effect to treatment with 5-fluorouracil (5-FU), but the underlying mechanisms are not fully understood. The objective of this systematic review was to evaluate the pathophysiology of 5-FU- induced cardiotoxicity. METHODS: We systematically searched PubMed for articles in English using the search terms: 5-FU OR 5-fluorouracil OR capecitabine AND cardiotoxicity. Papers evaluating the pathophysiology of this cardiotoxicity were included. RESULTS: We identified 27 articles of 26 studies concerning the pathophysiology of 5-FU-induced cardiotoxicity. The studies demonstrated 5-FU-induced: hemorrhagic infarction, interstitial fibrosis and inflammatory reaction in the myocardium; damage of the arterial endothelium followed by platelet aggregation; increased myocardial energy metabolism and depletion of high energy phosphate compounds; increased superoxide anion levels and a reduced antioxidant capacity; vasoconstriction of arteries; changes in red blood cell (RBC) structure, function and metabolism; alterations in plasma levels of substances involved in coagulation and fibrinolysis and increased endothelin-1 levels and N-terminal-pro brain natriuretic peptide levels. Based on these findings the proposed mechanisms are: endothelial injury followed by thrombosis, increased metabolism leading to energy depletion and ischemia, oxidative stress causing cellular damage, coronary artery spasm leading to myocardial ischemia and diminished ability of RBCs to transfer oxygen resulting in myocardial ischemia. CONCLUSIONS: There is no evidence for a single mechanism responsible for 5-FU-induced cardiotoxicity, and the underlying mechanisms might be multifactorial. Further research is needed to elucidate the pathogenesis of this side effect.